Relationship between learning style and readiness for self-directed learning among nursing students at king Saud university, Saudi Arabia - AbuAssi, Nesreen; Alkorashy, Hanan (International Journal of Advanced Nursing Studies, 2016)
Self-directed learning and other prevalent learning styles are important aspects of nursing education because they help nurse educators to predict differences in learnersâ€™ needs, abilities, and interests. Moreover, nurse educators depend on these predictors when they choose the most suitable teaching strategies, which enable them to manage adult learners effectively. This studyâ€™s objective is to explore the relationship between learning styles and the willingness to adopt self-directed learning among nursing students in King Saud University (KSU). Using a cross-sectional descriptive correlational design, the study was conducted with 230 undergraduate nursing students (female and male) from the third to eighth academic levels at the College of Nursing at KSU, Saudi Arabia. Kolbâ€™s learning styles inventory and the self-directed learning readiness scale were adopted to determine the effects of the self-directed learning approach. The studyâ€™s findings suggested that the majority of nursing students had a â€œDivergingâ€ style of learning. The â€œself-controlâ€ subscale was used to determine the willingness for self-directed learning. It recorded the highest mean score compared to the subscales of â€œself-managementâ€ and â€œdesire for learning.â€ However, no statistically significant association was found between learning styles and self-directed learning readiness. Additionally, the findings showed that the majority of the students who participated in this study had little interest in the self-directed learning approach. Thus, this study recommends that the nursing faculty needs to assess students for their preferred learning style and readiness for self-directed learning before and throughout the studentsâ€™ enrollment in the college. Further, the nursing faculty should apply a variety of teaching methods to manage studentsâ€™ learning needs effectively.